2021
DOI: 10.1007/s40615-021-00982-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in COVID-19-Related Testing and Healthcare Utilization by Race and Ethnicity in the Veterans Health Administration

Abstract: Importance Recent reports indicate differences in COVID-19-related care and outcomes between Black and White Americans. Objective We examine the COVID-19-related healthcare utilization and mortality by race and ethnicity of patients tested for SARS-CoV-2 in the Veterans Health Administration (VHA). Design A retrospective cohort study. Setting We used the VHA COVID-19 shared data resources between February 1 and Jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Escobar et al found that Asian American, BA/AA, and HI/LA individuals (in Kaiser Permanente Northern California) had higher odds of COVID-19 infection compared to non-HI/LA White individuals, but that there were no differences across racial and ethnic groups in mortality among hospitalized patients [26]. A retrospective study conducted in the US Department of Veterans Affairs by Razjouyan et al found higher testing positivity rates and increased risk of hospitalization due to COVID-19 among BA/AA and HI/LA veterans, but also found that among those hospitalized there were no differences across race and ethnic groups in intensive care utilization or death [27]. Khanna et al found, in the population of patients served by the University of Maryland family medicine and immediate care, BA/AA patients and HI/LA patients were more likely to experience COVID-19 infection than non-HI/LA White patients [28].…”
Section: Resultsmentioning
confidence: 99%
“…Escobar et al found that Asian American, BA/AA, and HI/LA individuals (in Kaiser Permanente Northern California) had higher odds of COVID-19 infection compared to non-HI/LA White individuals, but that there were no differences across racial and ethnic groups in mortality among hospitalized patients [26]. A retrospective study conducted in the US Department of Veterans Affairs by Razjouyan et al found higher testing positivity rates and increased risk of hospitalization due to COVID-19 among BA/AA and HI/LA veterans, but also found that among those hospitalized there were no differences across race and ethnic groups in intensive care utilization or death [27]. Khanna et al found, in the population of patients served by the University of Maryland family medicine and immediate care, BA/AA patients and HI/LA patients were more likely to experience COVID-19 infection than non-HI/LA White patients [28].…”
Section: Resultsmentioning
confidence: 99%
“…First, as we expected, overall wait times increased substantially during the COVID-19 period. This finding is consistent with other studies 15 , 23 , 41 , 42 , 43 and is not surprising, given that substantial numbers of US residents delayed or went without care, particularly early in the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Our team, as well as others, showed that mortality and poor clinical outcomes in COVID-19 are linked to the presence of comorbid conditions as assessed by Charlson Comorbidity Index [ 11 , 31 ]. Our data shows that prior to or after adjustment for comorbid conditions using CCI; mortality remains significantly lower in Omicron compared to the two other study variants.…”
Section: Discussionmentioning
confidence: 99%
“…This is a retrospective cohort study that includes all Veterans who tested positive for SARS-CoV-2 between 1 February 2020 and 7 July 2022 and were hospitalized related to COVID-19 infection. The inclusion criteria were the first positive test and hospital admission within 7 days after the SARS-CoV-2 test date or within 15 days prior to the test date [ 10 , 11 , 12 ]. The exclusion criteria were not being veterans and not being an active VHA healthcare user.…”
Section: Methodsmentioning
confidence: 99%